Bisnis Komunikasi dan Sosial Media - Destri Natania Ruben; Alika Nur Halisa; Audina Fatihah Syakila; Kayla Zibandani; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study explores the critical implications of Corporate Social Media (CSM) use in the workplace, focusing on two main issues. First, it examines the phenomenon of corporate social media creep and the culture of “likes,” which generate presence bleed and participatory panoptic surveillance. These dynamics encourage conformity and surface-level phatic communication, thereby constraining the critical discussion and innovation essential for building sustainable competitive advantage. Second, the study investigates the integration of digital technologies and the mobilization of celebrity capital within advertising ecosystems through processes of influencer celebrification. While these new generative, collaborative, and evaluative practices offer opportunities for transparency and accountability, they also carry the risk that similar surveillance logics may produce rigid compliance, ultimately dampening employees’ productive potential. The study concludes that organizations must move beyond merely symbolic uses of CSM toward strategic implementations that limit creep, design incentives for critical content, and adopt governance mechanisms that prevent excessive surveillance, so that digital technologies can genuinely foster transformative knowledge exchange.